High Performance Computing for Tumor Propagation Agent-based Model - Tashakor, Ghazal (2017)
Agent based modeling (ABM) and High Performance Computing (HPC) techniques are very popular in investigation and understanding cellular and molecular systems. The complex nature of these systems and the demand for emulation and comprehension at different levels in these models creates the expectation for new effective simulation strategies and tools. The present paper peruses the foresaid demands and the approaches for developing simulation in tumor model and its interactions using ABM and HPC. ABM allows the analysis of the actions and interactions of autonomous agents (cells in this case) to evaluate their effects on the system as a whole in order to re-create and predict the appearance of a complex phenomenon. This is a parametric model and it is necessary to explore the data model space to determine which combinations of adjustments cause the behaviors which are of interest. In this case, HPC is a useful tool to perform experiments in acceptable time.